Tax compliance and information provision: A field experiment with small firms - Philipp Doerrenberg; Jan Schmitz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We study tax compliance in Slovenia using data generated in a field experiment. Small accounting companies were randomly assigned to an untreated control group and two treatment groups. Companies in the first treatment group received a letter that highlighted the importance of paying taxes and informed about the likelihood of becoming subject to an audit. In the second treatment group, tax officers from the tax authorities handed out in person the same letter that companies in the first treatment group received by post. The results indicate that such letters can increase compliance, and trigger even more compliance if handed over in person. These findings are in line with the theoretical predictions that we derive to rationalize the experiment.
urn:nbn:de:bsz:180-madoc-391883
Keywords: H20; H32; H50; C93; 330; Tax Compliance; Audits; Randomized Field Experiment; Tax authority; Information provision